Normal and tangential behaviour of dry joints in refractory masonry - Oliveira, Rafael Luiz Galvão (2021)
Industrial vessels used in high temperature processes of steel and cement production are protected by refractory linings built with mortarless joints. These dry joints, formed by stacked bricks have a crucial importance on the mechanical behaviour of the lining. The stiffness and consequently the stresses generated by thermal expansion are reduced due to the joints. The present article presents the results of experimental and numerical tests on the thermomechanical behaviour of these joints. The compressive strength of the brick was assessed at ambient and high temperatures and a statistical analysis of the distribution of the bricks’ shape imperfections was carried out. Several studies were carried out on the normal behaviour of the joints: classical joint closure test; bed joint closing action in a masonry wallet measured with a DIC; effects of brick’s height imperfections on its loadbearing capacity; effects of brick’s height imperfections on the wall’s behaviour at ambient and high temperatures and a comparison between the bed and head joints behaviour. To characterize the joint’s tangential behaviour at high temperatures a novel device was developed and presented.